Energi Terbarukan dari Jerami Padi : Review Potensi dan Tantangan Bagi Indonesia - Agus Haryanto; Siti Suharyatun; Winda Rahmawati; Sugeng Triyono (PERTETA, 2019)
Straw is a waste produced from the threshing and harvesting of rice. So far, rice straw has only been removed. In fact, it can be used as a potential energy source. This paper aims to examine the potential of rice straw as a renewable energy source in Indonesia. Opportunities and challenges were evaluated based on extensive and in-depth literature review. The paper discussed rice straw potential, its characteristics and benefits of using straw energy. Technology to convert rice straw into energy was also discussed. Results showed that renewable energy potential of rice straw is 28.8 TJ/year. Conversion technologies that can be applied include densification, combustion, gasification, and biogas. The biggest challenge for using rice straw energy is collection and transportation. Densification may overcome density problem by producing high quality pellets or briquettes that reduce transportation and storage costs. Straw characteristics need to be improved to increase its combustion properties.